Exploring Raw Red Clay as a Supplementary Cementitious Material: Composition, Thermo-Mechanical Performance, Cost, and Environmental Impact - Mohammed Drissi; Othmane Horma; Ahmed Mezrhab; Mustapha Karkri (Buildings)
This study explored the potential of natural red clay as a supplementary cementitious material (SCM) to reduce greenhouse gas emissions and costs associated with the cement industry. Given that cement production is one of the largest contributors to global greenhouse gas emissions, developing sustainable alternatives is of paramount importance. Recognizing the environmental impact of cement production, this research investigates the substitution of conventional cement with raw red clay, aiming to balance mechanical performance with enhanced thermal properties and a lower environmental footprint. Through chemical characterization using X-ray Fluorescence (XRF), along with comprehensive mechanical and thermal performance testing, this study identifies the dual role of raw clay in mortar. It was found that incorporating up to 5% by weight of raw clay slightly impacted compressive strength while significantly improving thermal conductivity and diffusivity, cost-efficiency, and environmental sustainability, making it an appealing option for structural applications requiring high mechanical resistance. Conversely, a higher proportion of clay (beyond 5%) compromises compressive strength, but further enhances thermal properties and environmental benefits, suggesting its suitability for applications where low mechanical resistance is acceptable. This investigation highlights the viability of raw clay as a promising SCM, offering a pathway to more sustainable construction materials without the need for energy-intensive processing, thereby contributing to the reduction in the construction sector’s carbon footprint and energy demand.